Community first response and out-of-hospital cardiac arrest: a qualitative study of the views and experiences of international experts. Issue 3 (23rd March 2021) - Heffernan, Eithne; Mc Sharry, Jenny; Murphy, Andrew; Barry, Tomás; Deasy, Conor; Menzies, David; Masterson, Siobhan
Abstract : Objectives: This research aimed to examine the perspectives, experiences and practices of international experts in community first response: an intervention that entails the mobilisation of volunteers by the emergency medical services to respond to prehospital medical emergencies, particularly cardiac arrests, in their locality. Design: This was a qualitative study in which semistructured interviews were conducted via teleconferencing. The data were analysed in accordance with an established thematic analysis procedure. Setting: There were participants from 11 countries: UK, USA, Canada, Australia, New Zealand, Singapore, Ireland, Norway, Sweden, Denmark and the Netherlands. Participants: Sixteen individuals who held academic, clinical or managerial roles in the field of community first response were recruited. Maximum variation sampling targeted individuals who varied in terms of gender, occupation and country of employment. There were eight men and eight women. They included ambulance service chief executives, community first response programme managers and cardiac arrest registry managers. Results: The findings provided insights on motivating and supporting community first response volunteers, as well as the impact of this intervention. First, volunteers can be motivated by 'bottom-up factors', particularly their characteristics or past experiences, as well as 'top-down factors', including culture and legislation. Second, providing ongoing support, especially feedback and psychological services, is considered important for maintaining volunteer well-being and engagement. Third, community first response can have a beneficial impact that extends not only to patients but also to their family, their community and to the volunteers themselves. Conclusions: The findings can inform the future development of community first response programmes, especially in terms of volunteer recruitment, training and support. The results also have implications for future research by highlighting that this intervention has important outcomes, beyond response times and patient survival, which should be measured, including the benefits for families, communities and volunteers.